A Good Surrogate: The Experiences of Women who are Gestational Surrogates in Canada. - Fisher, Ann M.; Hoskins, Marie M. (Canadian Journal of Counselling and Psychotherapy, 2013)
This study focused on gestational surrogates’ overall experiences of engaging in third party reproduction. In-depth interviews were conducted in order to understand the various ways that these women narrated the diverse challenges they encountered. The findings suggest women may benefit from more support to deal with several issues post delivery. Counsellors have a role to play in supporting women through this identity shift before, during, and after the gestational surrogate pregnancy by being aware of various discourses that impinge on the experience.